PRAKTIK PSYCHOLOGY INDIGENOUS DALAM PENDIDIKAN PESANTREN KHR. ASAD SYAMSUL ARIFIN PONDOK PESANTREN SALAFIAH SYAFI’IYAH SUKOREJO SITUBONDO - Mudafiatun Isriyah; Qurroti Ayun (Fakultas Adab dan Humaniora UIN Imam Bonjol Padang, 2022)
This study aims to reveal and describe how Indigenous Psychology KHR practices. As'ad Syamsul Arifin at the Salafiah Syafi'iyah Islamic Boarding School Sukorejo Situbondo (P2S4). This study focuses on the description of the implementation of Indigenous Psychology and literature in P2S4, using a qualitative approach of the ethnographic-hermeneutic type. Sources of data used: primary data and secondary data reinforced by interviews with informants. Data analysis: data reduction, data display, and conclusion drawing. The results of the study: learning practices carried out: 1) The practice of indigenous psychology in P2S4 is based on Islamic values ??(fiqh norms and Sufistic life systems) as well as local cultural values, oriented to the benefit of the people, the formation of akhlaqul karimah which always invites goodness. , prevent evil, and fear God Almighty, 2) development, testing, and very little data, psychological theories are assumed to be universal, 3) impose their views on ordinary people: ta'zir, ta'dib, i 'tibar ahwal an-nas, at-tadrij, 4) The original concepts have been analyzed as examples of indigenous psychology. These concepts are interesting, they have limited communicative value for thinkers who do not understand language or know direct phenomena. Also, it is difficult to ascertain whether these conceptualizations are accurate and to assess the scientific merits of these original concepts because very little empirical evidence exists to support their claims. Research suggestions, (1) can be popularized and published in indigenous psychology education in P2S4, (2) the results of this study can be practiced for counselors in Islamic boarding schools, (3) other researchers conduct a more in-depth study of Indiginous Psychology with other focuses to find common ground in different contexts.